Self-care practices and use of medicinal plants by elderly individuals with type 2 diabetes mellitus in a Brazilian rural community - Bárbara Mendes Guimarães; Jandesson Mendes Coqueiro; Dilceu Silveira Tolentino Júnior; Amanda Soares Gama; Beatriz Magalhães; Lúcia Pedroso Lucas; Gracimério José Guarneire; Márcio Coutinho de Souza; Caio Cesar de Souza Alves; Alessandra de Paula Carli (Discover Public Health)
Abstract Introduction There is evidence that self-management improves health outcomes and quality of life for elderly patients with type 2 diabetes mellitus (T2DM) worldwide. This study aimed to evaluate self-care practices and the use of medicinal plants in elderly individuals with T2DM living in the rural area of Teófilo Otoni, Minas Gerais, Brazil. Methods This is a cross-sectional study with a quantitative approach, carried out between February and November 2021. A total of 181 diabetic elderly individuals aged 60 years or older, of both sexes, registered in Basic Health Units (BHU) throughout the rural area of the municipality were interviewed using the Self-Care Activities Questionnaire, adapted from the Summary of the Diabetes Self-Care Activities Questionnaire (SDSCA), with the addition of items related to the investigation of alcoholism and the use of medicinal plants for the treatment of DM2. A literature review of the list of herbal species used for the treatment of diabetes was carried out using indexed articles. Results We found that 67.9% (n = 127) were women, 44.2% (n = 80) had low levels of education, 45.3% (n = 82) were between 60 and 69 years old, and 71.3% (n = 129) declared themselves black or brown. Of these, 90.6% used the medication indicated for diabetes 6–7 days a week, 92% took proper care of their feet, although they had lower adherence to self-care practices related to monitoring blood glucose levels and performing specific physical exercise. Tobacco was not consumed by 93.4% (n = 169) of the elderly in the last 7 days. Active smokers represented 6.6% (n = 12); on the other hand, alcoholism was the most frequent, with 87.3% (n = 158) having consumed some type of alcoholic beverage in the last 7 days before the interview. Regarding the use of medicinal plants, there was low adherence to this practice among the interviewees. Conclusion The results demonstrate the need for strategic actions that encourage the improvement of these subjects' self-care, and an important contribution to the promotion of public policies on the safe use of medicinal plants in the treatment of DM2, in addition to constituting insights to stimulate future research in this field of knowledge.